Ergosterone ameliorates RRR-induced spleen deficiency by gut microbiota-gut metabolites and P38MAPK signaling pathway - Liu, Ying; Bao, Haiying (Frontiers in Microbiology, 2025)
Spleen deficiency is an important immune and digestive system change. Ergosterone (ER) is bioactive steroid; however, to date, no relevant studies have explored its potential efficacy in treating spleen deficiency. The aim of the present study was to investigate the therapeutic effects and mechanism of action of ER on spleen deficiency syndrome induced by Rhei Radix et Rhizoma (RRR). RRR was used to induce the development of a spleen deficiency rat model to observe changes in body weight and pathological changes in organ tissues. Additionally, the levels of relevant immune factors and gastrointestinal hormones were measured, as well as the expression of intestinal tight junction proteins and the P38MAPK signaling pathway. Changes in intestinal microbiota and metabolites were measured, and the effect of ER on the RRR-induced spleen deficiency rat model was evaluated. ER notably alleviated the symptoms of RRR-induced spleen deficiency induced in rats and offered protection against organ damage. Ergosterone can increase the expression of immunoglobulins, inhibits the increase in inflammatory factors, improve gastrointestinal hormone disorders, protect the intestinal mucosa, and repair intestinal barrier damage. The ER-treated group exhibited substantial upregulation of claudin and occludin mRNA and protein expression levels in the colonic tissue. Additionally, ER inhibited the P38MAPKsignaling pathway, thereby improving RRR induced spleen deficiency syndrome in rats. ER also influences the metabolic pathways of protein digestion and absorption, biosynthesis of unsaturated fatty acids, and arachidonic acid metabolism. In addition, ER can regulate and enhance the composition of intestinal flora in rats with spleen deficiency, increase the diversity of dominant flora, and inhibit the proliferation of harmful bacteria. ER can treat spleen deficiency syndrome by enhancing immune function, improving gastrointestinal function, repairing the intestinal barrier, and regulating intestinal flora and intestinal metabolites.